Estudio para determinar el factor vocacional en enfermería ante la pandemia de COVID-19 - Morandín-Ahuerma, Fabio (2021)
Objectives: To assess whether the SARS-Cov2 (COVID-19) pandemic is a relevant factor [y = f (x)] that negatively influences the vocation of nurses. Materials and method: The present mixed, cross-sectional, non-experimental study had n = 392 participants (85% women and 15% men) from 99 institutions of the public and private Health Sector (83%), as well as from educational centers (17% ) from Mexico, Spain, Cuba and Peru. An online survey with 10 multiple-choice items and an open question was applied. Results: Regarding the variable Vocation against Covid-19, although 50.3% are afraid of contagion, only 19% have thought to leave. With other correlations, mixed data were obtained that allow the analysis of work contexts, emotions, experiences and conditions that promote or weaken work and spirit of service in the nursing area.